Dynamics of macroparticle in a weakly collisional plasma - Romashchenko, E.V.; Bizyukov, A.A.; Girka, I.О. (Вопросы атомной науки и техники, 2019)
The transport of a macroparticle (MP) in an expanding cathodic vacuum arc plasma, which interacts with a background gas, is investigated. The influence of ion-neutral collisions on MP is studied in the framework of self-consistent model based on the fluid approach and orbital motion limited theory. It is found that the electrostatic re-flection of MP increases with collisionality as a consequence of the increased negative potential of MP. A compari-son of the ion drag and neutral drag forces governing the MP dynamics is made. It is shown that the ion drag force decreases with the ion collisionality, while the neutral drag force increases.